ANALYSIS OF PRODUCT INNOVATION MODELS IN INCREASING CUSTOMER INTEREST IN BMT TUNAS HARAPAN SYARIAH - Muhammad Sapwan (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2024)
The aim of this research is to determine the product innovation model in increasing customer interest in BMT Tunas Harapan Syariah. To find out more deeply, what innovation models are used by BMT to increase customer loyalty. Researchers also used qualitative research methods, where the research results showed that the existing innovation model at Tunas Harapan Syariah showed that the procedures and processes were easier. Where customers are pampered by BMT both in terms of service system and so on. There are three products innovated by BMT, such as: education savings, marriage savings, qurban savings. Where in these three products innovation was carried out by providing bonuses which created improvements both in terms of customers and improvements for BMT. The obstacles experienced in innovating products at BMT Tunas Harapan Syariah are the old system so that customers do not know and do not understand the system.